Programming in HTML and PHP: Coding for Scientists and Engineers - Brooks, David R (Undergraduate Topics in Computer Science, 2017)
This concise and accessible textbook will enable readers to quickly develop the working skills necessary to solve computational problems in a server-based environment, using HTML and PHP. The importance of learning by example (as opposed to simply learning by copying) is emphasized through extensive use of hands-on exercises and examples, with a specific focus on useful science and engineering applications. The clearly-written text is designed to be simple to follow for the novice student, without requiring any background in programming or mathematics beyond algebra.Topics and features: describes the creation of HTML pages and the characteristics of HTML documents, showing how to use HTML tables, forms, lists, and frames to organize documents for use with PHP applications; explains how to set up a PHP environment, using a local or remote server; introduces the capabilities and syntax of the PHP language, including coverage of array syntax and use; examines user-defined functions in programming, summarizing PHP functions for reading and writing files, viewing the content of variables, and manipulating strings; reviews the PHP GD graphics library, presenting applications for creating pie charts, bar graphs, and line graphs suitable for displaying scientific data; includes appendices listing HTML and ASCII special characters, and highlighting the essential basic strategies for solving computational problems.Supplying all of the tools necessary to begin coding in HTML and PHP, this invaluable textbook is ideal for undergraduate students taking introductory courses in programming. The book will also serve as a helpful self-study text for professionals in any technical field.